PENINGKATAN KECERDASAN KINESTETIK MELALUI PEMBELAJARAN GERAK DASAR TARI MINANG - YUNINGSIH, RESTU (Jurnal Pendidikan Usia Dini, 2015)
Abstract: Purpose of research to increase kinesthetic intelligence in early childhood through learning basic dance movements minang. The research was conducted on a group B1 Kindergarten 01 River State Capping the number of 12 children, was conducted from March to April 2015. This study used action research methods (Action research) by Kemmis and Taggart. This study consisted of two cycles, each cycle consisting of 8 sessions / actions. Data analysis using quantitative and qualitative data. Quantitative data analysis with descriptive statistics that compare the results obtained from the first cycle and the second cycle. Analysis of qualitative data by analyzing data from the field notes and interviews during the study to the steps of data reduction, data display and data verification. At 48.07% pre-cycle, the first cycle increased to 63.54% and the second cycle into 85.12%. The results showed an increase kinesthetic intelligence in early childhood B1 group carried through learning basic dance movements minang. Keywords: Kinesthetic Intelligence, Dance Movements Minang